Effect of mixing some specific fungicides with calcium and boron on control grey mold Botrytis cinerea to tomato under greenhouses - علاف, عصام (Latakia University Journal -Biological Sciences Series, 2022)
This study aimed at the effect of calcium and boron to control grey mold disease of tomato in greenhouses by mixing with specific fungicides. The experiment was conducted in greenhouse in Yahmour (Tartous) department on January 2021. Tomato plants were sprayed by Powmyl, Powmyl and Defazeem, leaf fertilizer (contains calcium and boron) with the last two treatments, and control. The result show that the fertilizer addition increased the two fungicides activity in controlling grey mold insignificantly the first ten days after spray, then it became significant after twenty days of spray, the additive value of infection decreased from 1.2 to 0.2 when the fertilizer mixed with Powmyl, and from 0.56 to 0.13 when it mixed with Powmyl and Defazeem. Calcium and boron effect on mycelium of grey mold causal agent and increase the resistance of plant to infection due to increasing the cell wall thickness.